Improving Students’ English Skills through Peer Tutoring Method - Pudiyono; Titi Wahyukti; Atik Muhimatun A; Zulfa Nabila; Akhmad Nurhadi (JURNAL INOVASI EDUKASI, 2021)
The purpose of the research is to improve students’ English skills through Peer Tutoring Method. The research was conducted in order to solve the problem encountered in the classroom; the students lack of interested in English. The design of this research was qualitative. It was obtained through observation and questionnaire tests. The writers apply them to know the improvement of students’ English skills through Peer Tutoring Method. Through questionnaire tests, the writers reflected students’ performance in a meeting for the second cycle. The writers took 2 cycles. The subjects of this research were third semester of University of Ma’arif Nahdlatul Ulama Kebumen in academic year 2022/2023. On first cycle, students felt bored, lack of confidence, and common mistake in English. On second cycle, the students’ motivation increased, students’ enthusiastic increased, and students’ English skills increased. The result of this research showed the using of peer tutoring method in the teaching and learning process was effective to improve students’ English skills.